Influence of high-load shocks on achieving mainstream partial nitrification: Microbial community succession - Chenjie Jia; Jialin Li; Zhaoyang Li; Liang Zhang (Water Research X)
Driving microbial community succession through the regulation of operational strategies is crucial for achieving partial nitrification (PN) in municipal wastewater. However, at present, there is a decoupling between the strategic regulation of PN systems and the succession characteristics of the microbial community. This study examined the correlation between microbial community succession and PN performance under two high-load shocks (HLS1 and HLS2) treating actual sewage. During HLS1, the influent organic loading rate (OLR) and nitrogen loading rate (NLR) increased from 116.7 ± 37.7 to 219.7 ± 24.7 mg COD/(g VSS·d) and 0.21±0.02 to 0.33±0.02 kg N/m3/d respectively, with the nitrite concentration and nitrite accumulation ratio only reaching 11.7 ± 2.7 mg/L and 49.3 ± 13.9 %, respectively. During HLS2, the influent OLR and NLR increased from 123.5 ± 17.2 to 300.3 ± 49.2 mg COD/(g VSS·d) and 0.19±0.03 to 0.32±0.03 kg N/m3/d respectively, resulting in a nitrite accumulation ratio of 89.4 ± 10.7 %. The system achieved efficient PN performance and sustained for 124 days. High-throughput sequencing results showed that community diversity remained consistently high, and the community composition returned to its initial state following a minor succession during HLS1. During HLS2, the high-load shock reduced the richness and evenness of the microbial community. The community underwent succession in a new direction, leading to community composition and function changes. The results indicate that the realization, stabilization, and disruption of PN are influenced not only by operational parameters but also by microbial community structure.